28.0k views
2 votes
sing the definition of the​ derivative, find f'(x). Then find f'(1)​, f'(2)​, and f'(3)when the derivative exists. f(x)=-x^2+4x-9

User Li Che
by
5.2k points

1 Answer

1 vote

By definition of the derivative, and with
f(x)=-x^2+4x-9, we have


f'(x)=\displaystyle\lim_(h\to0)\frac{f(x+h)-f(x)}h

In this case,


f(x+h)=-(x+h)^2+4(x+h)-9=-x^2-2xh-h^2+4x+4h-9=f(x)+(4-2x)h-h^2

Then


f(x+h)-f(x)=(4-2x)h-h^2


\implies\frac{f(x+h)-f(x)}h=4-2x-h

so that as
h\to0, we're left with


f'(x)=4-2x

and so


f'(1)=2


f'(2)=0


f'(3)=-2

User Sanji
by
5.3k points